ULTRASTRUCTURAL ANALYSIS OF GRUNT FIN (GF) CELLS TREATED WITH RED SEA BREAM IRIDOVIRUS (RSIV; family Iridoviridae, genus Megalocytivirus) IN COMBINATIONS WITH INTERFERONS AND SPLENIC SUBSTANCES - Ketut Mahardika; Teruo Miyazaki (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2010)
The genus Megalocytivirus in the family of Iridoviridae encompasses isolate of red sea bream iridovirus (RSIV). In the present study, grunt fin (GF) cells were treated with red sea bream iridovirus (RSIV) in combinations with interferons (IFNs) and splenic substances. The viral titer in the combination with primary splenic substance was higher than the other combinations of 10-1 and 10-2 diluted splenic substances, and the positive control. The viral titer was not decreased by all combinations with recombinant murine interferon-α (rMuIFN-α), recombinant murine IFN-β (rMuIFN-β), and recombinant feline interferon-ω (rFeIFN-ω). Electron microscopy revealed inclusion body bearing cells (IBCs) and enlarged cells allowing virus propagation within the intracytoplasmic virus assembly site (VAS). Most were enlarged cells. These enlarged cells were divided into three cell types. Cells of Type II, which contained many mature virions within the VAS, were numerous in number in all treated cells. Cells of Type I allowing assembly of few virions and cells of Type III containing many immature viral particles were rather fewer in number. Their percentage was almost the same in all combinations with the splenic substances and IFNs. These results determined in in vitro treatment with IFNs did not prevent viral replication of RSIV, as well as the splenic substances which were derived from the RSIV-infected spleen of red sea bream did not contain any factors to disturb RSIV replication.